„Świat przebrany, nieprzebrany”. Metafora tekstylna w poezji Stanisława Barańczaka - Czaja, Kamila (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article discusses the issue of textile metaphor and its function in Stanisław Barańczak’s poetry – a topic that used to be discussed mainly in relation to women’s poetry. In his poems, Barańczak uses elements of garments as a means to capture abstract and often dangerous aspects of existence and as a symbol of a system or a characteristic of citizens living in a specific time. Textile metaphor allows him to expose the falsehood of the system and the threat of totalitarianism, while also constituting part of a dissident’s everyday equipment. References to parts of garments are a way to present the poetic programme and the ambiguous role of an artist. In a ‘disguised’ and dangerous world of poetry marked by a secret difficult to ‘uncover’, one is, in a way, sentenced to dress against the requirements imposed on them by reality.